2021
DOI: 10.1002/mde.3431
|View full text |Cite
|
Sign up to set email alerts
|

Can the SO2 emission trading system promote urban emission reduction?

Abstract: Preliminary explorations have been conducted on the SO2 emission trading system (ETS) in China, but existing studies have paid little attention to the system's emission reduction effect and the effect mechanism. Based on panel data of Chinese cities, this paper empirically examines the influence and mechanism of the SO2 ETS on urban SO2 emission. In addition, considering the role of government in local environmental governance, this paper also examines synergies between government environmental regulations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Equation mainly examines the effect of international students on urban innovation based on a two‐way fixed‐effect model. Considering the dynamic characteristics of the effect of international students on urban innovation at different levels, we follow Goff et al (2019) and Yang et al (2021) to use the quantile regression model to investigate the dynamic track of the impact of international students on urban innovation. In Equation , q is the quantile 0.25emα1,q reflecting the marginal effect of international students on urban innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Equation mainly examines the effect of international students on urban innovation based on a two‐way fixed‐effect model. Considering the dynamic characteristics of the effect of international students on urban innovation at different levels, we follow Goff et al (2019) and Yang et al (2021) to use the quantile regression model to investigate the dynamic track of the impact of international students on urban innovation. In Equation , q is the quantile 0.25emα1,q reflecting the marginal effect of international students on urban innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang Shengling et al (2021) showed that ETS achieves environmental optimization by increasing green total factor productivity (GTFP) and reducing investment in pollution-intensive industries in pilot provinces, confirming the existence of Porter's hypothesis and the investment transfer transmission path [45]. Yang S. et al (2021) showed that ETS promotes urban SO 2 reduction by stimulating green technology innovation, promoting industrial restructuring, and directing investment toward green assets. Among them, the mediating effect of directing investment toward green assets is the strongest [46].…”
Section: Literature Reviewmentioning
confidence: 96%
“…Yang S. et al (2021) showed that ETS promotes urban SO 2 reduction by stimulating green technology innovation, promoting industrial restructuring, and directing investment toward green assets. Among them, the mediating effect of directing investment toward green assets is the strongest [ 46 ]. Because of the spatial spillover effect of the harm caused by the accelerated SO 2 emissions [ 47 ], Du Gang et al (2021) showed that ETS significantly stimulated green utility innovation in and around the pilot areas and that there was a masking effect of government intervention in the process [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, for innovation input, commonly used measurement indicators include R&D investments and personnel (Brown et al, 2009;Yang, Wang, et al, 2022). In terms of innovation output, a commonly used indicator is the number of patents owned by the enterprise (Hall & Harhoff, 2012;Yang et al, 2021). Patent output is the final embodiment of the various innovation factors used as inputs (Shahzad et al, 2021;Su & Liu, 2021;Yang, Ma, & Lu, 2022).…”
Section: Variable Selectionmentioning
confidence: 99%